A Retrospective and Prospective Examination of the 1960s U.S. Northeast Drought. Issue 7 (27th July 2021) - Xue, Zeyu; Ullrich, Paul
Abstract: As the most severe drought over the Northeastern United States (NEUS) in the past century, the 1960s drought had pronounced socioeconomic impacts. Although it was followed by a persisting wet period, the conditions leading to the 1960s extreme drought could return in the future, along with its challenges to water management. To project the potential consequences of such a future drought, pseudo‐global warming simulations using the Weather Research and Forecasting Model are performed to simulate the dynamical conditions of the historical 1960s drought, but with modified thermodynamic conditions under the shared socioeconomic pathway SSP585 scenario in the early (2021–2027), middle (2041–2047), and late (2091–2097) 21 st century. Our analysis focuses on essential hydroclimatic variables including temperature, precipitation, evapotranspiration, soil moisture, snowpack, and surface runoff. In contrast to the historical 1960s drought, similar dynamical conditions will generally produce more precipitation, increased soil moisture and evapotranspiration, and reduced snowpack. However, we also find that although wet months get much wetter, dry months may become drier, meaning that wetting trends are most significant in wet months but are essentially negligible for extremely dry months with negative monthly mean net precipitation. For these months, the trend toward wetting conditions provides little relief from the effects of extreme dry months. These conditions may even aggravate water shortages due to an increasingly rapid transition from wet to dry conditions. Other challenges emerge for residents and stakeholders in this region, including more extreme hot days, record‐low snow pack, frozen ground degradation and subsequent decreases in surface runoff. Plain Language Summary: The 1960s Northeastern United States (NEUS) drought was an abnormally long period of low precipitation, recognized for its impacts on agriculture and the water supply. Although cold temperatures at the time did partially mitigate its impacts, under a changing climate there is a risk of much warmer temperatures exacerbating these impacts. To better understand the impacts from a reoccurrence of the 1960s drought, we study a scenario in which the weather patterns of this period return in the context of a warmer future environment. Our results show that subject to similar weather patterns, the NEUS will be much wetter, with increases in both precipitation and soil water. However, these wetter conditions are only apparent in moderate and moderately wet months; in extremely dry months, future water availability is largely unchanged, or even decreases from the analogous historical months. Further, future precipitation has more variability and drought tends to initiate more quickly. Additional challenges emerge with more extremely hot days, more severe extreme precipitation, reduced snowpack, loss of frozen soil, and subsequent loss of runoff. Our results are useful for guiding future policymaker and stakeholder decisions in light of climate uncertainty. Key Points: 1960s drought conditions are simulated under early, mid, and late 21 st century warming A significant wetting trend emerges; however, it helps little to mitigate the extreme dry months Significant snowpack loss and surface runoff decrease are anticipated for future droughts